Electrical-stress driven oxidation in 940 nm oxide-confined VCSEL. (10th December 2021) - Pusterhofer, Michael; Fabbro, Robert; Coppeta, Raffaele A; Fasching, Gernot; Hadley, Peter
Abstract: In this work, accelerated stress tests have been performed on oxide confined vertical cavity surface emitting LASER arrays to study the formation of defects degrading the performance of the device. One such defect is an additional oxide volume forming at the oxide aperture edge, which is used for optical and electrical confinement. After producing an additional oxide volume the sample was investigated using transmission electron microscopy to estimate the oxidation speed. To produce further insights into the formation process, the temperature during such a stress test was estimated by experimentally measuring the thermal resistance, and by a thermodynamic transport simulation. Both methods produced very similar results showing a temperature increase of around 22 K for a dissipated power of 3.5 mW per emitter. However this temperature rise is very small when compared to oxidation models found in literature and should not be enough to promote the oxidation. This indicates the presence of a new enhanced oxidation mechanism, which could be connected to corrosion based failure mechanisms reported in literature.